A review on individual differences and cultural intelligence - Che Rose, Raduan; Kumar, Naresh; Sri Ramalu, Subramaniam (2008)
In the pace of globalization, it is crucial that individuals have the knowledge and skills to effectively face the challenges and requirements of a “global village”. It is believed that cultural intelligence (CQ) explains why some individuals are more capable at navigating culturally diverse environments than others. Prior research has indicated that CQ role is highly significant in predicting cross-cultural effectiveness among expatriates.However, as a new and quickly growing area of research factors that influence CQ is still under researched. This article proposes the influence of stable dispositions and dynamic competencies as the antecedents of CQ. The theoretical and practical implications are discussed.